The consequences of vehicle hijacking - Davis, L (Social Work/Maatskaplike Werk, 2025)
Although incidents of vehicle hijacking are spiralling world-wide, vehicle hijacking has been identified as a priority crime in South Africa. The status it has acquired is directly related to the serious implications it holds for the individual in terms of the physical, emotional, financial and social consequences associated with it, as well as the negative local and international response it elicits. The inclusion of violence or threats of violence, as well as the theft of a vehicle in definitions of vehicle hijacking, often leads to confusion regarding the classification whereby hijacking is alternatively classed as either a violent crime or a property crime. This may be attributed to the fact that vehicle hijacking is primarily a form of theft as a vehicle is taken from the victim, thus constituting a property crime. In this regard researchers (Block, 1989:235; Steenkamp, 1997:19) emphasise that during a robbery the primary aim is not to injure the victim, but to obtain valuable goods such as a vehicle. On this basis police and members of the criminal justice system as well as those in the helping professions often treat such victims as victims of a property crime (i.e. in the same manner as burglary victims) without acknowledging the trauma they have experienced. Lack of knowledge of the fact that violence and threats of violence are used to facilitate the robbery, and that hijacking without an element of violence is not a possibility, often leads to these important elements being ignored. A further reason for this may be inadequate knowledge about the serious consequences of vehicle hijacking. The aim of this exposition is therefore to shed some light on the position of trauma victims of vehicle hijacking experience, to emphasise the far-reaching consequences of this priority crime, and to highlight some of the problems that are experienced with currently available support. This is done in the hope that such information will not only broaden the knowledge of social workers, but also encourage them and others in the helping professions to treat victims of vehicle hijacking in the same way as other victims of violent crimes.